Pengaruh Electronic Service Quality dan Electronic Word of Mouth Terhadap Keputusan Pembelian Kamar Di Aston Denpasar Hotel and Convention Center - Maureen Audria; I Nyoman Sudiksa; Ida Ayu Kalpikawati (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2021)
This study aimed to analyze the influence of Electronic Service Quality and Electronic Word of Mouth on Room Purchase Decisions at Aston Denpasar Hotel & Convention Center. The data were collected by distributing online questionnaires with the help of the hotel to respondents who were guests who had stayed at Aston Denpasar Hotel & Convention Center totaling 100 people. The data collected from the questionnaire were then analyzed using the classic assumption test, multiple linear regression analysis, t test, F test and coefficient of determination analysis. The results showed (1) electronic service quality had a positive and significant effect on room purchase decisions with a significance value of 0.011 <0.1 indicating that H01 was rejected and Ha1 was accepted (2) electronic word of mouth had an effect positive and significant impact on room purchase decisions with a significance value of 0.010 <0.1 indicating that H02 is rejected and Ha2 is accepted (3) electronic service quality and electronic word of mouth has a positive and significant effect on room purchase decisions with a significance value of 0,000 <0.1 indicate that H03 is rejected and Ha3 is accepted.